Outcomes of pericardiectomy for constrictive pericarditis following mediastinal irradiation. Issue 12 (21st September 2021) - Pahwa, Siddharth; Crestanello, Juan; Miranda, William; Bernabei, Annalisa; Polycarpou, Andreas; Schaff, Hartzell; Dearani, Joseph; Stulak, John; Pochettino, Alberto; Daly, Richard; Lahr, Brian; Viehman, Jason; et al.
Abstract: Background: Pericardiectomy for postradiation constrictive pericarditis has been reported to generally have unfavorable outcomes. This study sought to evaluate surgical outcomes in a large cohort of patients undergoing pericardiectomy for radiation‐associated pericardial constriction. Methods: A retrospective analysis of all patients (≥18 years) who underwent pericardiectomy for a diagnosis of constrictive pericarditis with a prior history of mediastinal irradiation from June 2002 to June 2019 was conducted. There were 100 patients (mean age 57.2 ± 10.1 years, 49% females) who met the inclusion criteria. Records were reviewed to look at the surgical approach, the extent of resection, early mortality, and late survival. Results: The overall operative mortality was 10.1% ( n = 10). The rate of operative mortality decreased over the study period; however, the test of the trend was not statistically significant ( p = .062). Hodgkin's disease was the most common malignancy (64%) for which mediastinal radiation had been received. Only 27% of patients had an isolated pericardiectomy, and concomitant pericardiectomy and valve surgery were performed in 46% of patients. Radical resection was performed in 50% of patients, whereas 47% of patients underwent subtotal resection. Prolonged ventilation (26%), atrial fibrillation (21%), and pleural effusion (16%) were the most common postoperative complications. The overall 1, 5‐, and 10‐years survival was 73.6%, 53.4%, and 32.1%, respectively. Increasing age (hazard ratio, 1.044, 95% confidence interval 1.017–1.073) appeared to have a significant negative effect on overall survival in the univariate model. Conclusion: Pericardiectomy performed for radiation‐associated constrictive pericarditis has poor long‐term outcomes. The early mortality, though high ( 10%), has been showing a decreasing trend in the test of time.